Fragments of drains retained during operations on the temporomandibular joint. Issue 3 (April 2019) - Hills, A.J.; Armstrong, D.; Bisase, B.; Norris, P.
Abstract: Drains are robust and reports of breakages and retained fragments are rare. There is no consensus about the management of such cases and we know of no reported cases. We present the case of an 18-year-old man with a retained drain fragment after repair of an open condyle.